Responses of Giving n-Hexane Jaloh Extract on Broiler Chicken which Heat Stress Condition to Expression of iNOS Enzyme in Lung Tissue, Serum level of Glucose and Calcium - Sugito, Sugito (Indonesian Animal Sciences Society, 2008)
Giving of extract n-hexane of jaloh bark (EHJ) can lessen impact heat stress on broiler chicken. The studies of activity of EHJ in lessening heat stress impact at broiler chicken have not been conducted yet. An experiment was conducted to study the effect of extract n-hexane of jaloh bark (EHJ) administration on body temperature, level of calcium and glucose in serum, inducible nitric oxide synthase (iNOS) in lung tissue, and behaviors of broilers exposed to heat stress at temperature 33 Â± 1oC. This study used 18 broilers aged 20 days which were divided into 3 groups. The first group was broilers given heat stress without EHJ (CP). The second group was treated heat stress and EHJ at dose 10 mg/kg BW (CP+EHJ). The EHJ was given 1 hour before cage temperature was raised. Broilers in group CP and CP+EHJ were divided into 3 periods of slaughtering i.e. 2 and 4 hours after given heat stress and 2 hours after heat stress termination. Each of slaughtering period consisted of 3 broilers as replication. Result of this research indicated that CP+EHJ lessen stress in the form of restlessness and increased expression of iNOS in the lung tissue. It was assumed that one of mechanism of EHJ in lessening stress on broiler related to forming of iNOS enzyme in the lung tissue. Key Words: Salix, Heat Stress, Calcium, Glucose, i-NOS Enzyme